Are biosimilars patentable?. (2nd August 2016) - Rolfe, Damian; Parker, Jayson; Morgan, Max
ABSTRACT: Introduction: This paper explores whether, and under what circumstances, a biosimilar approved in the United States under the Biologics Price Competition and Innovation Act (hereafter 'BPCIA') can be patented. The possibility that a biosimilar product could have meaningful patent protection arises from specific requirements for biosimilarity under the BPCIA, which account for the fact that manufacturing processes of biologics are inherently imprecise. The requirements for biosimilar approval may provide sufficient leeway to a biosimilar applicant to patent structural or formulation differences that provide non-clinical but business-relevant advantages over the reference molecule, such as improved shelf-life or ease of manufacture, without compromising clinical biosimilarity. Areas covered: Examination of the BPCIA and related Acts, Food and Drug Administration (FDA) guidance papers, case law, patent database searching, and relevant scholarly articles. Expert opinion: Legislative and regulatory requirements for the approval of a biosimilar under the BPCIA are focused on clinical results and allow a degree of leeway for differences to exist between a biosimilar's structure and non-clinical components and those of the biosimilar's reference molecule. This leeway can be exploited to provide the biosimilar with potentially patentable business-relevant advantages over its reference product while maintaining clinical biosimilarity to the reference product.